Major Improvement in the Cycling Ability of Pseudocapacitive Vanadium Nitride Films for Micro‐Supercapacitor. Issue 9 (15th January 2023) - Jrondi, Aiman; Buvat, Gaetan; Pena, Francisco De La; Marinova, Maya; Huvé, Marielle; Brousse, Thierry; Roussel, Pascal; Lethien, Christophe
Abstract: Vanadium nitride film made using a thin film deposition technique is a promising electrode material for micro‐supercapacitor applications owing to its high electrical conductivity and high volumetric and surface capacitance values in aqueous electrolyte. Nevertheless, the cycling stability has to be improved to deliver good capacitance during a large number of cycles. Here, it is shown that vanadium nitride films made by a magnetron sputtering deposition method exhibit remarkable cycling stability (high capacitance retention value after 150 000 cycles), ultra‐high rate capability (75% of the initial capacitance at 1.6 V s −1 ), while providing high surface capacitance values (≈1.4 F cm −2 ) and very low ageing of the VN electrodes (no loss of performance after 13 months). Additionally, new findings regarding the location of vanadium oxides species responsible for the charge storage mechanism in pseudocapacitive VN films are revealed by transmission electron microscopy electron energy‐loss spectroscopy analyses at the nanoscale. Abstract : Sputtered vanadium nitride film as an electrode material and current collector for micro‐supercapacitors is optimized to deliver high capacitance, high cycling stability, low ageing and high rate capability. The charge storage process occurring at the surface of vanadium oxides within the VN film is investigated. This study unveils the position of oxide species responsible for the pseudocapacitive behavior of the electrode.